Knowledge, attitude and practices regarding immunization among parents with children in the age group 12 to 24 months - Jayaraj, Jaippreetha; Ganesan, Swathi; Geminiganesan, Sangeetha (International Journal Of Community Medicine And Public Health, 2023)
Background: Immunization is one of the most indispensable community-based health interventions with unquestionable ability to improve a nation’s health status. In spite of evidences about the effectiveness of vaccines, millions of children around the world are lagging behind exposing them and their community to a risk of epidemics. Despite efforts taken to improve vaccination coverage, India has only succeeded in achieving 65% coverage in childhood immunization. We aim to determine parental knowledge, attitudes and practices regarding childhood immunization. Methods: It is a questionnaire-based observational study involving 95 parents with children aged 12 to 24 months, conducted in a tertiary care hospital in Tamil Nadu. Results: Ninety children have been completely immunized according to age. Nearly 60% children did not receive vaccinations according to prescribed schedule. More than half parents believed that vaccines are efficient in preventing diseases, which was statistically associated with education of parents. Although there is a good immunization coverage in our locality, 17.89% parents still doubt the safety of vaccines and one-fifth of respondents had misapprehensions that vaccines may cause long-term consequences in children. Conclusions: We found that multiple factors play a role in determining the immunization status of the population, including sociodemographic characteristics, level of knowledge and attitudes towards immunization. Therefore, improving knowledge, attitudes and practices regarding immunization among parents is one of the key initiatives towards building a disease-free nation.